2016
DOI: 10.1177/0192513x16638384
|View full text |Cite
|
Sign up to set email alerts
|

Does Earning More Than Your Spouse Increase Your Financial Satisfaction? A Comparison of Men and Women in the United States, 1982 to 2012

Abstract: Scholars have argued that both husbands and wives are less satisfied if wives outearn their husbands because this violates the norms of the male breadwinner model. Some scholars find support for this hypothesis when studying the division of household work, marital dissolution, or depression, but other scholars do not find clear evidence. This article adds to this literature by asking how people's roles in bringing money into the household (as a primary or secondary earner) affect how they feel about that money… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 66 publications
(86 reference statements)
0
16
0
Order By: Relevance
“…Instead, the negative association between a woman’s relative income and financial well-being results from traditional gender norms and breadwinning culture. Moreover, in a recent study of long-term US trends, Eirich and Robinson (2017) find little proof of resource exchange theory. They instead suggest that social psychological processes are the reason why individuals are more financially satisfied if they out-earn their partners, independent of gender.…”
Section: Financial Well-being and Intra-household Sharingmentioning
confidence: 92%
“…Instead, the negative association between a woman’s relative income and financial well-being results from traditional gender norms and breadwinning culture. Moreover, in a recent study of long-term US trends, Eirich and Robinson (2017) find little proof of resource exchange theory. They instead suggest that social psychological processes are the reason why individuals are more financially satisfied if they out-earn their partners, independent of gender.…”
Section: Financial Well-being and Intra-household Sharingmentioning
confidence: 92%
“…A study by Ahn et al (2014) finds that in Denmark, a highly gender-egalitarian society, both men and women report higher financial satisfaction when they contribute a greater share to household labour income, though for women this association is only significant for cohabiting and not married women. Similarly, in a US sample, the spouse with the higher relative income within the couple reports higher levels of satisfaction with the household’s financial situation, regardless of the respondent’s sex or their level of gender traditionalism (Eirich and Robinson, 2017). This goes against assumptions that gender norms are always trumped by economic considerations – at least with respect to financial satisfaction.…”
Section: Literaturementioning
confidence: 99%
“…They interpret the results "as illustrative of the expectations held for male economic behavior in traditional conceptions of marriage and the discontent that ensues when such expectations are unfulfilled" (Furdyna et al, 2008, p. 341). On the other hand, Eirich and Robinson (2016) find that full-time working married American individuals are more satisfied with their family's financial situation when they earn more money than they spouse -whether they are women or men. However, the authors have also found that traditional gender ideology does not moderate this association, and they conclude that social comparison processes (relative deprivation) can trump the traditional prescription of the male breadwinning role.…”
mentioning
confidence: 94%
“…Previous research on this issue used Western European and American data (Ahn et al, 2014;Bertrand et al, 2015;Bonke, 2008;Eirich and Robinson, 2016;Furdyna et al, 2008;Rogers and DeBoer, 2001). It has found mostly negative associations between women's relative income and men's financial or marital happiness, whereas the results are mixed and less conclusive for women.…”
Section: Introductionmentioning
confidence: 99%